Disciplinary action against judges according to subclause “b” of clause 1 of article 106 of the law of Ukraine on the judiciary and the status of judges - Stratonov, Vasyl; Rybalko, Volodymyr (Archives of Criminology and Forensic Sciences, 2023)
Using specific examples (in particular from the practice of the Grand Chamber of the Supreme Court), the research analyzes and describes which offenses by a judge are classified under subclause “b” of clause 1 of Article 106 of the Law of Ukraine On the Judiciary and the Status of Judges (omission to include the reasons for accepting or rejecting the arguments of the parties on the merits of the dispute into the court decision). Research papers have been reviewed and information regarding the development and current state of this issue has been provided. Controversial issues of applying this ground for disciplinary action have been considered. Based on statistical data, the dynamics of its implementation have been traced. The paper will be useful not only for disciplinary inspectors and judges but also for complainants since it will help understand which specific violations are prospective in terms of appealing a judge’s behavior to the High Council of Justice under subclause “b” of clause 1 of Article 106 of the Law of Ukraine On the Judiciary and the Status of Judges.